Energy efficiency in academic buildings through optimization and operational strategies - Albadarneh, Mousa Jamal Salem (2021)
Building energy efficiency is significant to reduce energy consumption of buildings. This leads reduction of greenhouse gas effects, healthy environment, and increment in electrical efficiency with an excellent cost effect. Optimizing the lighting system is one of the operational strategies in increasing the buildings energy efficiency. In this study, attempts were made to measure, and evaluate existing internal lighting system, to maximize the energy efficiency which focused on the Faculty of Mechanical Engineering (FKM) first floor, located at Universiti Teknikal Malaysia Melaka (UTeM). Retrofitting through simulation using DIALux software was done by comparing the performance of the fluorescent and LED luminaire. Physical parameter requirements (illuminance, lighting intensity) were compared to current Malaysian standard (Malaysian Standard 1525: 2014). The result for this project provides a pattern in lighting distribution and human comfort parameters. The study also analyzed the effects of luminaires type used at the comfort level of the occupants and investigated the impact of lighting on the illuminance, universal glare rating, and uniformity values. The illuminance values for current system are far from MS1525, so the vision is uncomfortable for occupants, especially in class rooms. Retrofit of lighting system in the FKM’s first floor is necessary, so a new lighting system was proposed by replacing fluorescent with the LED luminaires. The deviation between predicted data, and experimental measurements of the average illuminance were between 23.4% and 29.9% and uniformity were between 11.08% and 17.21%. The comparison between Fluorescent, and LED luminaires in terms of illuminance, unified glare rating, and color rendering index were done based on Malaysian standards values, and uniformity based on European standards.